2007
DOI: 10.1016/j.ejcts.2007.01.017
|View full text |Cite
|
Sign up to set email alerts
|

Operative complications and early mortality after induction therapy for lung cancer

Abstract: Induction therapy seems to be associated with an increased incidence of air leakage; the risk of other complications is acceptable. Pneumonectomy is associated with an increased risk of mortality and should be performed in selected patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
37
2
6

Year Published

2008
2008
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(51 citation statements)
references
References 20 publications
6
37
2
6
Order By: Relevance
“…Risk of induction chemotherapy in surgery with an extent of less than pneumonectomy Despite the absence of randomised trials having as end-point the impact of chemotherapy on the post-operative outcome of resections less than pneumonectomy, recent evidence resulting from retrospective and prospective studies [249][250][251][252][253][254] has shown acceptable morbidity and mortality rates in selected patients.…”
Section: Chemo-radiotherapy In Lung Cancermentioning
confidence: 99%
“…Risk of induction chemotherapy in surgery with an extent of less than pneumonectomy Despite the absence of randomised trials having as end-point the impact of chemotherapy on the post-operative outcome of resections less than pneumonectomy, recent evidence resulting from retrospective and prospective studies [249][250][251][252][253][254] has shown acceptable morbidity and mortality rates in selected patients.…”
Section: Chemo-radiotherapy In Lung Cancermentioning
confidence: 99%
“…Hino (50) showed that octogenarians with postoperative morbidity had significantly poorer prognosis than those without it. A number of risk factors for developing postoperative morbidity have been reported: congestive heart failure, myocardial infarction, male gender, type of operative procedure, extended lymph node dissection, FEV 1 of 40% or less, smoking status, stroke (3,26,27,42) and administration of induction therapy (51). For all these reasons, a "customized" preoperative assessment to identify physiological or pathological frailty should be encouraged since standard tools may be less reliable.…”
Section: General Considerationsmentioning
confidence: 99%
“…8 Similarly, Venuta et al observed a mortality rate of 12.5% (4/32) for patients who received neoadjuvant therapy and concluded that pneumonectomy should only be performed in carefully selected patients. 9 However, Alan et al report a low postoperative mortality rate of 5.6% and conclude that there is no significant increase in postoperative mortality after pneumonectomy in those who received neoadjuvant chemotherapy. 10 Similarly, Ng et al did not observe any significant difference in postoperative mortality between the group that underwent neoadjuvant therapy (with no mortalities out of 17 patients) and the group that did not receive neoadjuvant therapy.…”
Section: Resultsmentioning
confidence: 99%